2015
DOI: 10.1016/j.celrep.2015.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Lam6 Regulates the Extent of Contacts between Organelles

Abstract: SummaryCommunication between organelles is crucial for eukaryotic cells to function as one coherent unit. An important means of communication is through membrane contact sites, where two organelles come into close proximity allowing the transport of lipids and small solutes between them. Contact sites are dynamic in size and can change in response to environmental or cellular stimuli; however, how this is regulated has been unclear. Here, we show that Saccharomyces cerevisiae Lam6 resides in several central co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
214
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(224 citation statements)
references
References 19 publications
8
214
0
2
Order By: Relevance
“…Consistent with the localization of Ltc1 at ER-mitochondria contact sites, two other research groups identified Ltc1 as an interactor with the ERMES complex based on proteomic analyses (118,119). The absence of Ltc1 alone did not impair growth on fermentable or nonfermentable carbon sources or affect mitochondrial morphology or assembly of the ERMES complex; however, it did aggravate the growth defect of ERMES mutants, suggesting that Ltc1 and ERMES fulfill different roles toward mitochondrial functionality (118,119).…”
Section: Multiple Roles For Ermes In Mitochondrial Biologymentioning
confidence: 56%
See 2 more Smart Citations
“…Consistent with the localization of Ltc1 at ER-mitochondria contact sites, two other research groups identified Ltc1 as an interactor with the ERMES complex based on proteomic analyses (118,119). The absence of Ltc1 alone did not impair growth on fermentable or nonfermentable carbon sources or affect mitochondrial morphology or assembly of the ERMES complex; however, it did aggravate the growth defect of ERMES mutants, suggesting that Ltc1 and ERMES fulfill different roles toward mitochondrial functionality (118,119).…”
Section: Multiple Roles For Ermes In Mitochondrial Biologymentioning
confidence: 56%
“…The absence of Ltc1 alone did not impair growth on fermentable or nonfermentable carbon sources or affect mitochondrial morphology or assembly of the ERMES complex; however, it did aggravate the growth defect of ERMES mutants, suggesting that Ltc1 and ERMES fulfill different roles toward mitochondrial functionality (118,119). Murley et al (118) showed that the majority of Ltc1 localized at ER-mitochondria MCSs with about half colocalizing with ERMES foci.…”
Section: Multiple Roles For Ermes In Mitochondrial Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…Ltc1p (also known as Lam6p), an ER integral membrane protein, is localized to NVJ via its binding to Vac8p (31,33). Another integral ER membrane protein, Mdm1p, binds vacuolar phosphatidylinositol-3-phosphate through its PX domain, forming NVJs (32).…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian MAMs are formed by protein tethers, similar to the tetrameric tethering complexes in fungi known as ER-mitochondria encounter structures (ERMES) (Kornmann et al, 2009). However, of the more than 30 proteins involved in vertebrate MAM function, only two of them, GRAMD1A, which corresponds to yeast Lam6p, and MIRO (also known as RHOT1), which corresponds to yeast Gem1p, are conserved in ERMES (Kornmann et al, 2011;Elbaz-Alon et al, 2015). This increased complexity of animal MAMs suggests they acquired new roles beyond those controlled by ERMES (HerreraCruz and Simmen, 2017).…”
Section: Introductionmentioning
confidence: 99%